Microwave-assisted hydrothermal synthesis and gas sensing properties of ZnSn(OH)6, ZnSnO3, and Zn2SnO4/SnO2 hierarchical nano-/hetero-structures - Masteghin, Mateus G. [UNESP]; Silva, Ranilson A. [UNESP]; Orlandi, Marcelo O. [UNESP] (Elsevier, 2024)
Although semiconducting metal oxide sensors present reasonable sensitivity, an improved lower detection limit and/or selectivity would allow broadening real-time monitoring applications. This work reports the growth mechanism and gas sensing performance of zinc tin oxide-based structures synthesised via a microwave-assisted hydrothermal route. The synthesised materials were characterised by X-ray diffraction (XRD), Raman and Fourier-transform infrared (FTIR) spectroscopy, scanning and scanning transmission electron microscopy (SEM and STEM), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDS), and nitrogen adsorption/desorption experiments. Gas sensor measurements showed that ZnSnO3 presents an outstanding lower detection limit to nitrogen dioxide (NO2), in which a 10-fold increase in electrical resistance is expected in the presence of 1 ppb NO2 at an operating temperature of 150 ˚C. Moreover, the Zn2SnO4/SnO2 heterostructure exhibited superior selectivity to NO2 relative to hydrogen (H2) and carbon monoxide (CO), exhibiting a sensor response ∼1500 times higher for the oxidising gas. Hence, it is demonstrated that nanostructures’ growth engineering can realise lower detection limits and ultra-selective high-performance gas sensor devices through a greater surface area and enhanced contact potential barriers.
Keywords: Hydrothermal synthesis; Metal oxide gas sensor; Nitrogen dioxide sensing; Tin oxide; Zinc tin hydroxide; Zinc tin oxide